Flipped classroom model for teaching Bahasa Indonesia in higher education - Pitoyo, Andri; Lailiyah, Nur (Journal of Educational Management and Instruction (JEMIN), 2024)
This study aimed to design and evaluate a flipped classroom model for Bahasa Indonesia learning in higher education. It explores the potential challenges of implementing the flipped classroom in Bahasa Indonesia language teaching in a university setting. Employing a mixed method, this study combined both qualitative and quantitative approaches. In the first stage, a flipped classroom model for Bahasa Indonesia language learning was designed, considering pedagogical, technological, and contextual aspects. The model was implemented over a six-week course. Qualitative data were collected through classroom observations, interviews with lecturers and students, and document analysis. Quantitative data were obtained using pre- and post-intervention to assess students' perceptions and performance. The results showed that the flipped classroom model had a positive impact on student motivation and engagement in Bahasa Indonesia learning. However, challenges were also identified, such as the availability of quality digital resources and mastery of technology by lecturers and students. The findings of this study contribute to the development of innovative and effective Bahasa Indonesia teaching practices in higher education and provide insights for the development of the flipped classroom model in other language learning contexts.